2022
DOI: 10.3390/v14020395
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A(H1N1)pdm09 Virus but Not Respiratory Syncytial Virus Interferes with SARS-CoV-2 Replication during Sequential Infections in Human Nasal Epithelial Cells

Abstract: The types of interactions between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and other respiratory viruses are not well-characterized due to the low number of co-infection cases described since the onset of the pandemic. We have evaluated the interactions between SARS-CoV-2 (D614G mutant) and influenza A(H1N1)pdm09 or respiratory syncytial virus (RSV) in the nasal human airway epithelium (HAE) infected simultaneously or sequentially (24 h apart) with virus combinations. The replication kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…Our observation supports possible SARS-CoV-2 dominance via unique host interactions as well as the potential occurrence of priming the immune system to limit co-infection [4]. Symptomatic testing demand was higher during the first year of the pandemic with weekly averages of 38.5, 95% CI [35.8, 41.2], daily orders, yet the weekly average SARS-CoV-2 positive cases of 1.6, 95%CI [1.4, 1.7] may further indicate the activity of another pathogen during that time.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our observation supports possible SARS-CoV-2 dominance via unique host interactions as well as the potential occurrence of priming the immune system to limit co-infection [4]. Symptomatic testing demand was higher during the first year of the pandemic with weekly averages of 38.5, 95% CI [35.8, 41.2], daily orders, yet the weekly average SARS-CoV-2 positive cases of 1.6, 95%CI [1.4, 1.7] may further indicate the activity of another pathogen during that time.…”
Section: Discussionsupporting
confidence: 77%
“…Our observation supports possible SARS-CoV-2 dominance via unique host interactions as well as the potential occurrence of priming the immune system to limit co-infection [4]. Symptomatic testing demand was higher during the first year of the pandemic with weekly averages of 38.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, it has been demonstrated that hRV triggers an interferon response that blocks SARS-CoV-2 replication ( 28 ). Influenza Virus, but not RSV, reduced SARS-CoV-2 replication and in turn, SARS-CoV-2 interfered with RSV-A replication in Nasal Epithelial Cells in vitro ( 29 ). Accordingly, it is possible to hypothesize that RSV circulation this year was halted by the ongoing spread of the SARS-CoV-2 Omicron variant surge that was particularly contagious and abundant in unvaccinated children ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…and Fage et al. studied the interference between RV, RSV, influenza and SARS-CoV-2 by simultaneous or sequential infection in the human ALI culture system ( Essaidi-Laziosi et al., 2022 ; Fage et al., 2022 ). While both studies indicated the effect of influenza in suppressing the subsequent SARS-CoV-2 replication and both of them suggested that the viral interference was dependent on interferon pathways but not related to blockage of viral entry, the effect of SARS-CoV-2 in inhibiting the subsequent infection of influenza virus diverged in these two studies.…”
Section: Discussionmentioning
confidence: 99%